2022
DOI: 10.1038/s41598-022-18263-z
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight convolutional neural network for aircraft small target real-time detection in Airport videos in complex scenes

Abstract: Airport aircraft identification has essential application value in conflict early warning, anti-runway foreign body intrusion, remote command, etc. The scene video images have problems such as small aircraft targets and mutual occlusion due to the extended shooting distance. However, the detection model is generally complex in structure, and it is challenging to meet real-time detection in air traffic control. This paper proposes a real-time detection network of scene video aircraft-RPD (Realtime Planes Detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The AP represents the average detection accuracy of the model for a class of obstacles, and the mAP refers to the average detection accuracy of the model for all kinds of obstacles. The calculation formulas are shown in ( 7 )–( 10 ), where TP denotes the number of positive samples correctly predicted by the model, FP represents the number of positive samples incorrectly predicted by the model, FN expresses the number of negative samples incorrectly predicted by the model, and P i is the corresponding accuracy rate of n positive samples of a certain class of obstacles 30 , 31 . …”
Section: Methodsmentioning
confidence: 99%
“…The AP represents the average detection accuracy of the model for a class of obstacles, and the mAP refers to the average detection accuracy of the model for all kinds of obstacles. The calculation formulas are shown in ( 7 )–( 10 ), where TP denotes the number of positive samples correctly predicted by the model, FP represents the number of positive samples incorrectly predicted by the model, FN expresses the number of negative samples incorrectly predicted by the model, and P i is the corresponding accuracy rate of n positive samples of a certain class of obstacles 30 , 31 . …”
Section: Methodsmentioning
confidence: 99%
“…Aircraft object detection based on video images primarily involves extracting feature maps through convolutional neural networks (CNN), fusing features, and finally outputting detection results [7]. Figure 1 illustrates the developed algorithm flow.…”
Section: A Principles Of Yolov5mentioning
confidence: 99%
“…Evaluation of the detection performance of the developed model involved metrics such as precision (P), mean average precision (mAP), and recall (R) [19], as expressed in Eqs. (5)(6)(7).…”
Section: B Model Trainingmentioning
confidence: 99%
“…Zhao et al [ 25 ] suggested a multiscale information augmentation framework (MS-IAF), which accurately identifies multiscale aircraft and their vital parts by stacking perceptual fields of various scale sizes in a multipath way. Li et al [ 26 ] developed a new core component CBL module to increase the receptive field range in the neural network in order to address the issue of aircraft detection in airport field video images that is caused by a long shooting distance, small aircraft targets, and mutual occlusion. Wu et al [ 27 ] enhanced aircraft detection in high-resolution remote sensing images with dense targets and complex backgrounds by improving Mask-rcnn [ 28 ] based on atrous convolution.…”
Section: Related Workmentioning
confidence: 99%